Implementasi Algoritma Simple Additive Weighting (SAW) dalam Menentukan Supplier Bahan Pokok Makanan - Tria Hadi Kusmanto; Ahmad Fauzi; Eko Harli (Jejaring Penelitian dan Pengabdian Masyarakat (JPPM), 2025)
The experience and subjective opinions of restaurant management are the only factors used in the manual supplier selection process. Uncertainty about product availability and quality, higher costs, and difficulty managing supplier relationships are just a few of the issues that can arise from this approach. Finding a balance between product quality and price is a common challenge when selecting suppliers. Restaurants must consider suppliers' prices and ensure they align with the quality of the food they serve. A multi-criteria research method for selecting restaurant suppliers is the Simple Additive Weighting (SAW) algorithm. Each relevant supplier selection criterion must be ranked and weighted according to this procedure. By using the Simple Additive Weighting (SAW) method, a decision support system for restaurant supplier selection can simplify and accelerate the supplier selection process and provide timely and accurate reporting.